Keeping the Kingdom: The Politics of Higher Education Reform in Saudi Arabia - Nolan, Leigh. (2017)
Abstract: As the forces of globalization accelerate, Saudi Arabia is entering the 21st century with immense pressure on its traditional ruling balance. Possessing a largely statist economy, a growing youth demographic and the societal pressures attendant with rapid social and technological change, it is crucial to understand the possibilities and limits of the Al Saud monarchy's ability to adapt to meet these challenges. This dissertation focuses on the question of how institutional reform occurs in a monarchy. Is it possible for rigid systems to transition and transform themselves, short of political upheaval, to be more flexible and responsive? To do so, this dissertation will examine the trajectory of reform in a key soft institution of the state, the higher education sector, in Saudi Arabia. The process of Saudi Arabia's higher education reform and its negotiation of religious, political, and regional actors is perhaps the most fraught in the Gulf region due to its accelerated pace of development, deep religious traditions, and the complex political dynamics of the Kingdom. This dissertation examines Saudi Arabia's higher education reform model through process tracing and field work in the Kingdom to highlight the institutional and societal mechanisms that are essential to modernization in the region, the challenges such reform faces and ask how, in the face of significant political pressure against education reform, reform is initiated and implemented. The majority of literature on liberalization in the Middle East has focused on formal political reform, yet Gulf Arab Oil Monarchies have been largely resistant to democratization, even as they embark on ambitious societal and bureaucratic reform. How they actually pursue institutional reform and to what degree is a largely unexplored terrain in political development literature on the Middle East. My research contributes to this literature by examining the actual bargaining process and political dialogue surrounding the institutional reform of the higher education sector in Saudi Arabia.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Andrew Hess.; Committee: Anna Seleny, and Ibrahim Warde.; Keywords: Middle Eastern studies, and International relations.